Degradation behaviors of geometric cues and mechanical properties in a 3D scaffold for tendon repair. Issue 4 (8th February 2017) - Wu, Yang; Wong, Yoke San; Fuh, Jerry Ying Hsi
Abstract: A three‐dimensional (3D) scaffold fabricated via electrohydrodynamic jet printing (E‐jetting) and thermally uniaxial stretching, has been developed for tendon tissue regeneration in our previous study. In this study, more in‐depth biological test showed that the aligned cell morphology guided by the anisotropic geometries of the 3D tendon scaffolds, leading to up‐regulated tendious gene expression including collagen type I, decorin, tenascin‐C, and biglycan, as compared to the electrospun scaffolds. Given the importance of geometric cues to the biological function of the scaffolds, the degradation behaviors of the 3D scaffolds were investigated. Results from accelerated hydrolysis showed that the E‐jetted portion followed bulk‐controlled erosion, while the unaixially stretched portion followed surface‐controlled erosion. The 3D tendon scaffold exhibited consistency between the weight loss and the decline of mechanical properties, which indicated by a 65% decrease in mass with a corresponding 56% loss in ultimate tensile strength after degradation. This study not only reveals that the anisotropic geometries of 3D tendon scaffold could affect cell morphology and lead to desired gene expression toward tendon tissue but also gives an insight into how the degradation impacts geometric cues and mechanical properties of the as‐fabricated scaffold. © 2017 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 105A: 1138–1149, 2017.